PENGEMBANGAN BUKU CERITA SAINS BERGAMBAR UNTUK PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) KELAS III SEKOLAH DASAR - Wijaya, I Komang Wisnu Budi; Wahyuni, Ni Nyoman Tri; Yasa, I Made Wiguna; Suastini, Ni Nyoman; Santi, Ening Manika (Dharmas Education Journal (DE_Journal), 2024)
This study aims to develop a science storybook with illustrations for teaching science (IPAS) to third-grade elementary school students and test the validity and practicality of the developed science storybook. This research is classified as research and development. It follows the 4D model stages: define, design, develop, and disseminate. The study was conducted at SD Negeri 5 Mas Ubud, Gianyar Regency, Bali Province. The research instruments used include a validity sheet and a practicality sheet. The data from the research were analyzed descriptively. The results show that the developed science storybook consists of twelve science stories designed to introduce seven science concepts (IPAS), complete with animated illustrations, storyline, and science concept columns and the developed science storybook meets the requirements for validity and practicality. The conclusion of this research are a science storybook with illustrations is suitable for use in science learning.